Malkún Castillejo Willian, Educación y política en el Estado Soberano de Bolívar 1857-1885, Editorial Universitaria, Cartagena, 2013 (265). Págs. - Aguanche Rangel, Elle (Historia Caribe, 2013)
Reseña